GERD ANXIETY DAN TERAPI PENYEMBUHANNYA PERSPEKTIF Q.S. AL-BAQARAH: 153 - Mohammad Shodiq Ahmad; Hunaya Mumtazwina (Darul Hikmah: Jurnal Penelitian Tafsir dan Hadits, 2023)
Health is an expensive blessing from Allah SWT that is often forgotten by humans. The prevalence of GERD Anxiety disease today has become a new phenomenon among society. Stress factors play a major role in triggering GERD Anxiety. GERD Anxiety is a disease that is closely related to mental health. Therefore, GERD Anxiety is a complex disease with many factors that cause it. If the main cause is not treated, the healing process for GERD Anxiety will be more difficult and even worsen the sufferer's condition. The effects of stress will result in GERD Anxiety. Stress levels are increasing, so the prevalence of GERD Anxiety in society is also increasing. The connection between the digestive nerves and the brain nerves makes it a key role in human mental and physical health. In this research, it is applied in dealing with the treatment of physical and psychological illnesses using the perspective of Q.S. Al-Baqarah verse 153. The hypothesis in this research is to explain to the public what GERD Anxiety really is, and explain the study of the scholars' interpretation of Q.S. Al-Baqarah verse 153 and also determines how to treat GERD Anxiety. The method used in this research, seen from its type, uses qualitative research methods, by conducting library research. Meanwhile, the writing technique refers to the guidelines for writing Scientific Work (Thesis, Journal) of the Ushuluddin College of Science, Darul Hikmah, Bekasi, 2022 and the General Guidelines for Indonesian Spelling (PUEBI), 2016. The results of the research show that there are methods and treatments for treating GERD. Anxiety from a psychological perspective and the sufferer's stomach can be achieved through the Koran and Sunnah approach. In terms of spiritual medicine, it uses a spiritual ruhiyyah approach. Because basically, the Qur'an is syifa (medicine) for human spirituality and physicality and also a guide to life that humans can follow to overcome various kinds of problems in this world